PENGARUH KARAKTER EKSEKUTIF, KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Ratih Qadarti Anjilni; Fikri Fahrezi (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine how the Effect of Executive Character, Financial Performance and Company Size on Tax Avoidance. This research method uses associative quantitative, the object of research in manufacturing companies in the primary consumer goods sub-sector, using purposive sampling techniques in collecting data samples and the type of data used is secondary data. The total population in this study were 119 companies and a total sample of 28 companies so that 140 observation data were obtained in this study. The data analysis used in this study used panel data regression using the Eviews 12 test tool. The results showed that Executive Character, Financial Performance and Company Size had an effect on Tax Avoidance simultaneously, Executive Character and Company Size partially on Tax Avoidance while Financial Performance had no effect on tax avoidance. The benefits of this research are expected to be used as a means of information in accounting and taxation for the community.